La différenciation, une réponse individuelle et locale à une institution scolaire traversée de tensions - Sephora Boucenna
School is strongly criticized by a majority of its actors over its vulnerability and its fragmentation. To cope with these flaws and to uphold their function of educator, many teachers had to develop strategies such as differentiated instruction. Differentiated instruction holds an essential role in teaching even if each teacher assumes it in its own particular way. We decided not to treat diversification as a research concept but rather as a notion that urges their agents to take action they would not implement if they were not forced to do so by the substantial obstacles they encounter in their daily educators' life. Indeed, we interviewed seventeen teachers from elementary to under and post-graduate levels to explore, in a subjective approach, the elements in their practice that reveal implicit or explicit tensions that weakens the school system and makes school a stressful and uncomfortable place that can even generate pain.